Design of High-Performance Organic Nonlinear Optical and Terahertz Crystals by Controlling the van der Waals Volume - Shin, Bong Rim; Puc, Uros; Park, Yu Jin; Kim, Dong Joo; Lee, Chae Won; Yoon, Woojin; Yun, Hoseop; Kim, Chaeyoon; Rotermund, Fabian; Jazbinsek, Mojca; Kwon, O. Pil (Advanced Science, 2023)
In the development of new organic crystals for nonlinear optical and terahertz (THz) applications, it is very challenging to achieve the essentially required non-centrosymmetric molecular arrangement. Moreover, the resulting crystal structure is mostly unpredictable due to highly dipolar molecular components with complex functional substituents. In this work, new organic salt crystals with top-level macroscopic optical nonlinearity by controlling the van der Waals volume (VvdW), rather than by trial and error, are logically designed. When the VvdW of molecular ionic components varies, the corresponding crystal symmetry shows an observable trend: change from centrosymmetric to non-centrosymmetric and back to centrosymmetric. All non-centrosymmetric crystals exhibit an isomorphic P1 crystal structure with an excellent macroscopic second-order nonlinear optical response. Apart from the top-level macroscopic optical nonlinearity, new organic crystals introducing highly electronegative fluorinated substituents with strong secondary bonding ability show excellent performance in efficient and broadband THz wave generation, high crystal density, high thermal stability, and good bulk crystal growth ability.
Keywords: Centrosymmetric; Crystal structure control; Crystals structures; Non-centrosymmetric; Optical nonlinearity; Organic crystal; Performance; Structure control; Terahertz photonics; Van der Waals' volume; crystal structure control; nonlinear optics; organic crystals; terahertz photonics; van der Waals volume